Theories of Eliminative Induction - Nekrašas, Evaldas (Problemos, 1974)
The author analyses classical theories of eliminative induction and makes an attempt to determine the origins of some of the problems and solutions of modern analytic theories of induction. Induction theories of F. Bacon, J. F. W. Herschell and J. S. Mill are analysed, their interrelations and continuity are determined. Assumptions necessary to ground the effectiveness of the application of induction procedure are discussed. The question of interrelation between eliminative and enumerative induction is analysed in connection with the problem of the justification of induction. Finally, the conclusion is drawn that both classical systems of eliminative induction and R. Carnap’s inductive logic, notwithstanding their different conception of the goals of induction and the character of the inductive inference, are essentially atheoretical because of the common empiricist tradition they are based on.